Molecularly Imprinted Polymers (MIPs) - Sandesh Narayan Somnache (German Journal of Pharmaceuticals and Biomaterials)
MIPs, which stand for molecularly imprinted polymers, are biomimetic materials that have attracted much interest in various sectors, including healthcare. Antibodies and receptors are examples of physiologic recognition units that can be imitated by MIPs, which provides a fruitful platform for applications in biomedicine. The high specificity and selectivity of these molecules, along with their stability under critical conditions, long shelf life, and economic efficiency compared to commonly employed molecules, such as antibodies, proteins, and aptamers, are some of the attractive benefits they possess. There is the possibility of preparing MIPs for targets with no existing recognising molecules. However, their use in other research areas, such as biosensors, nanocarriers, and drug delivery systems, diagnostic and imaging, has also been substantial. MIPs have been employed for a variety of applications, the majority of which have been in the extraction and separation procedures. It is impossible to make these advancements without first generating novel polymers and monomers that can be successfully employed in MIP synthesis and can also improve the variety of applications for these compounds. A quick summary of MIPs is discussed, which interests the current editorial.